The aesthetics of organization - Linstead, Stephen, 1952-; Höpfl, Heather (SAGE Publications, 2000)
"Organizational aesthetics, both as a body of theory and a method of inquiry, is a rapidly expanding area of the organizational sciences. Bringing together the social sciences and humanities, artistic critical analysis and anthropological fieldwork, it offers a way forward from the puzzles of postmodernism and is an essential topic for organizational theorists and students of organizational behaviour." "This book draws together in an accessible style key foundational contributions delineating the emerging parameters of the field. It explains the significance of concepts devised by postmodern thinkers, through which emerge meaning and order in organizations." "The Aesthetics of Organization is a resource for students and researchers in organization and business studies."--Jacket.